Association between lipid profiles and Graves orbitopathy: A systematic review and meta analysis - Nanny Natalia Mulyani Soetedjo; Louis Fabio Jonathan Jusni; Eric Ricardo Yonatan; Steven Alvianto; Nicolas Daniel Widjanarko; Hikmat Permana (Endocrine and Metabolic Science)
Introduction: Graves orbitopathy (GO) is an autoimmune disorder affecting the tissues around the eyes, seen in 25–50 % of individuals with Graves disease (GD). Thyroid receptor antibodies (TRAb) target the TSH receptor, which can provoke an inflammatory response and promote fat cell formation by activating these receptors. Given this mechanism, statins that are commonly used for managing hyperlipidemia could be a potential treatment for GO. This review explores the connection between Graves orbitopathy and lipid profiles. Method: This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Articles were sourced from databases such as MEDLINE, ScienceDirect, EBSCO, ProQuest, Cochrane, and Google Scholar. The inclusion criteria covered both published and unpublished studies examining the relationship between GO and lipid profiles. Meta-analysis was conducted using Review Manager 5.4, and the risk of bias was evaluated using the Newcastle-Ottawa Scale (NOS). Result: This review included a total of four cross-sectional studies. All studies found a significant association between LDL cholesterol levels and Graves orbitopathy. However, the relationships with triglycerides (TG), HDL levels, and total cholesterol (TC) were not consistently statistically significant. The meta-analysis revealed significant differences in TC, LDL cholesterol, and TG levels across all groups (SMD = 0.48, CI = 0.17–0.80, p = 0.002, I2 = 67 %; SMD = 0.42, CI = 0.18–0.67, p = 0.0008, I2 = 47 %; SMD = 0.24, CI = 0.07–0.41, p = 0.005, I2 = 0 %, respectively), while HDL levels did not show significant differences among the groups (SMD = 0.16, CI = −0.02-0.34, p = 0.08, I2 = 10 %). Conclusion: Significant differences in serum lipid profiles, including TC, LDL, and TG except HDL, were found between patients with GO and those without. Further research is needed to confirm these findings.